Carcinoma in situ of the breast in New South Wales, Australia: Current status and trends over the last 40 year. (February 2018) - Jacklyn, Gemma; Morrell, Stephen; McGeechan, Kevin; Houssami, Nehmat; Irwig, Les; Pathmanathan, Nirmala; Barratt, Alexandra
Abstract: Background: The incidence of non-invasive breast cancer has increased substantially over time. We aim to describe temporal trends in the incidence of carcinoma in situ of the breast in New South Wales (NSW), Australia. Methods: Descriptive study of trends in the incidence of ductal carcinoma in situ (DCIS) and lobular carcinoma in situ (LCIS) in women who received a diagnosis from 1972 to 2012, recorded in the NSW Cancer Registry. Results: Carcinoma in situ as a proportion of all breast cancer was 0.4% during the prescreening period 1972 to 1987 and is currently 14.1% (2006 to 2012). Among 10, 810 women diagnosed with DCIS, incidence across all ages rose from 0.15 per 100, 000 during 1972 to 1983 to 16.81 per 100, 000 over 2006 to 2012, representing a 100-fold increase (IRR 113.10; 95% CI 81.94 to 156.08). Among women in the target age group for screening (50–69 years) incidence rose from 0.27 per 100, 000 to 51.96 over the same period (IRR 195.50; 95% CI 117.26 to 325.89). DCIS incidence peaks in women aged 60–69 years. DCIS incidence has not stabilized despite screening being well established for over 20 years, and participation rates in the target age range remaining stable. Conclusions: Our findings raise questions about the value of the increasing detection of DCIS and aggressive treatment of these lesions, especially among older women, and support trials of de-escalated treatment. Highlights: The transition from film to digital mammography is associated with an increase in the incidence of DCIS in women aged 50–69 years. The increase in incidence of carcinoma in situ has not been accompanied by a reduction in the incidence of invasive breast cancers. There is an important need to produce more evidence evaluating the clinical outcomes associated with de-escalation of treatment for DCIS.